1994
DOI: 10.1136/bmj.308.6938.1196
|View full text |Cite
|
Sign up to set email alerts
|

Ten year mortality in patients with suspected acute myocardial infarction

Abstract: urinary tract infection must be suspected, diagnosed, and treated rapidly in infancy and childhood and further infection prevented during follow up. It is also essential to identify vesicoureteric reflux early by investigation with cystography in infants with antenatal dilatation of the urinary tract, infants and young children after a first urinary infection, and siblings and offspring of patients with renal scarring. These measures will reduce the risk in children of the later development of reflux nephropat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…Our analysis shows that an annual mortality rate of about 2·6-3·3% can be anticipated in patients surviving their first myocardial infarction for 1 year. This annual mortality rate continues to be about twice as high as the reference population throughout 10 years, which is in agreement with another study [19] . When the parameters of infarct size or residual left ventricular function were included in the model, multivariate analysis did not indicate any contribution of thrombolytic therapy.…”
Section: Discussionsupporting
confidence: 92%
“…Our analysis shows that an annual mortality rate of about 2·6-3·3% can be anticipated in patients surviving their first myocardial infarction for 1 year. This annual mortality rate continues to be about twice as high as the reference population throughout 10 years, which is in agreement with another study [19] . When the parameters of infarct size or residual left ventricular function were included in the model, multivariate analysis did not indicate any contribution of thrombolytic therapy.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, apart from some isolated studies [2], the female sex has been found to be an independent predictor of worse prognosis in patients with coronary heart disease. This has been a consistent finding in a wide range of studies of first acute myocardial infarction [3] (AMI) and post-AMI periods [4] across numerous countries [5][6][7][8][9][10][11] and in reports of atypical presentation forms [12]. However, it remains unclear whether this higher mortality is explained by the higher age of females or presence of other risk factors, notably diabetes [13].…”
Section: Introductionmentioning
confidence: 69%
“…9 However, it is unclear to what extent this expenditure could have been avoided, since the standardised mortality ratio of patients admitted to hospital with suspected MI where a final diagnosis of 'no infarction' was made was found to be 4.7 [95% confidence interval (CI) 4.2 to 5.2] in the first year following the admission. 10 Therefore, it is likely that these patients do require investigation and treatment.…”
Section: The Evaluation Of Suspected Acsmentioning
confidence: 99%